Sweet, sticky, and sustainable social business - Ingram, V.J.; Njikeu, J. (2011)
African forest–based beekeeping has a long tradition, has been practiced in Cameroon for centuries, and contributes on average to 52% of household incomes of beekeepers in the Adamaoua savannah and Northwest montane forests. Livelihoods, regulatory and policy framework, business environment, and forest management are intricately linked in the chain from beekeeper to consumer. However, it has not been a route out of poverty; despite support, the majority of beekeepers subsist on $2 a day. An energetic, innovative, and entrepreneurial group named Guiding Hope is leading a new wave of indigenous social entrepreneurs revitalizing the apiculture sector with the aim of improving this situation. The story of how they developed, the challenges faced, and how they have translated multidisciplinary scientific findings into action is recounted. The combination of participatory action research, a value chain approach, monitoring, and learning from traditional knowledge has lead to positive societal and ecological benefits that extend from Cameroon to an international level.